The communicative status of an individual in a digital society - Yu. A. Chernavin (Цифровая социология, 2022)
The processes of digitalization of modern society are changing the significant ratio of its spheres and structures, bringing to the fore the communicative space, which appears as a system of communicative statuses of people, groups, organizations occupying a particular place in the structure of relevant relations. This circumstance determines the attempt to study this phenomenon in its application to human communicative interactions, made in the article from the standpoint of the theory of communicative action. Identity processes and alienation processes, both generating and limiting, subordinating the communicative activity of the individual, are considered as the basis for the emergence of the communicative status of the individual. Its contradictory nature is embodied in the transformations of the subject into the object of communicative influences and vice versa. In the course of the analysis undertaken within the framework of the activity approach, the essence and structure of the communicative status in the unity of its three elements are revealed: the communicative position of the individual; its communicative position (orientation); prestige as an assessment of a communicative position. The interacting elements of the status constitute its objective and subjective sides, localized simultaneously in two dimensions: digital virtual communicative space and real communicative space. The emerging duality of status is its most important characteristic in relation to the digital society. The peculiarities of the interaction of the objective and subjective in the digital space are revealed by analyzing, on the one hand, the phenomenon of a “digital double” created as a result of generalization of indicators of a person’s “digital footprint” regardless of his desire or unwillingness, on the other hand, the purposeful formation of an individual’s “avatar”. The generalized assessment of the communicative status of the individual leads to the conclusion that the characteristics of this phenomenon reflect the processes of individualization characteristic of digital society and indicate the desire of the individual to independently build his own communicative trajectory, the maximum realization of his capabilities as a subject of interactions.